L'architetto nell'amministrazione pubblica (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2017)
The discussions on the role of architects and engineers and their technical skills in public administrations are rarely addressed while usually the main attention is focused on the universities and teaching. This text tries to provide a contribution on this issue by reviewing in particular both collective and a personal experiences, carried out by architects and engineers in a local authority – in this case the municipality of Naples – which I believe can be considered exemplary to describe the transformation path of that role in the last decades of our Republic and to define possible perspectives.